(untitled) (Indian Journal of Animal Production and Management, 2024)
The present study was carried out on 18 crossbred LWY gilts and sows that were mated with suitable boars with the objectives to study the effect of various mating frequencies on various behavioural activities. They were randomly divided into 3 equal groups viz., Group I, II and III which were mated once, twice and thrice respectively with suitable boars, during a heat period and observed pre-coital and coital behavioural activities. Overall intermittent movement, slight forward movement, standing firmly were observed during, 5 (13.88%), 7 (19.44%) and 24 (66.66%) successful mating sessions, respectively. Gilts/sows exhibited frequent and partial vocalisation during 3 (8.33%), 10 (27.77%) mating sessions respectively out of total successful mating sessions. Gilts/ sows remained content during 22 (61.11%) successful mating sessions. Aggression, urinating and sniffing male genitalia was observed during 3 (8.33%), 11 (30.55%), 13 (36.11%) successful mating sessions out of total successful mating sessions. There was no significant difference between the groups. Overall mean of the primary changes in peri-partum behaviour viz., restlessness, grunting and anxiousness were observed 24.33 ± 3.16 h, 17.00 ± 3.11 h and 3.50 ± 0.64 h, respectively before farrowing. Overall mean of nest building behaviours viz., rooting & pawing, bar biting, chewing were observed 50.22 ± 4.47 h, 29.00 ± 2.66 h and 17.77 ± 1.41 h, before the birth of first piglet.